PENGARUH KEPUASAN KERJA DAN MOTIVASI EKSTRINSIK TERHADAP PRODUKTIVITAS KERJA MELALUI DISIPLIN KERJA PADA KARYAWAN PT. MESKOM AGRO SARIMAS KABUPATEN BENGKALIS - Suhada, Muhammad Fikri; Rama, Rovanita; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study carried out on PT. Meskom Agro Sarimas located at Pangkalan Batang Barat Kec. Bengkalis Kab. Bengkalis. Under the guidance of Dra. Nuryanti,M.Si and Rovanita Rama, SE., MH. This study aimed to determine The influence of job satisfying and extrinsic motivation on job performance throught work discipline of employee at PT. Meskom Agro Sarimas Bengkalis. Population on this study are employees of PT. Meskom Agro Sarimas Kab. Bengkalis AMDK division which amount of 103 people, with number of samples of 103 employees. Method of analysis used in this study is Path Analysis using SPSS version 20.0. The results of this study showed Job Satisfying (X1) has significant effect on Work Discipline (Y1), Extrinsic Motivation (X2) has significant effect on Work Discipline (Y1), Work Discipline (Y1) has Significant effect on Job Performance (Y2), Job Satisfying(X1) has significant effect on Job Performance(Y2) directly and indirectly throught Work Discipline (Y1), Extrinsic Motivation (X2) has significant effect on Job Performance(Y2) directly dan indirecly throught Work Discipline (Y1), and Work Discipline(Y1) has significant effect on Job Performance(Y2) of employee at PT.Meskom Agro Sarimas Bengkalis.Keywords : Job Satisfying, Extrinsic Motivation, Work Discipline, Job Performance